Rancang Bangun Sewa Kontrak Kios Pasar Dempo Permai Kota Pagar Alam Berbasis Web - Sasmita Sasmita (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2017)
Currently the progress of Information and Communication Technology has been adapted by various government agencies or private, one of the technology that can be used is web, government have used this technology for e-government. The Office of Industry, Trade and SME of Kota Pagar Alam that runs the Market through the Technical Implementation Unit of the Service gives the right to rent at Pasar Dempo Pagar Alam. During this time if there is an empty kiosk, prospective tenants come to the clerk for confirmation and lease submission process. To simplify the management and lease submission process, an application is needed that can facilitate the officer and prospective tenants to interact, while the application will be built is web-based. The purpose of this study design application in the sense of translating the results of the analysis into the form of software packages later Create the system or improve the existing system. To make the proposed system the author uses the steps of Customer Communication, planning, modeling, construction and deployment.